Disrespect and abuse of women during childbirth at health facilities in Eastern Africa: systematic review and meta-analysis - Gebeyehu, Natnael Atnafu; Adella, Gtachew Asmare; Tegegne, Kirubel Dagnaw (Frontiers in Medicine, 2023)
Background Disrespectful and abusive maternity care is a sign of poor treatment that influences women’s choice to deliver their babies in institutions. Such malpractices continue to go unreported and are rarely exposed in developing countries, despite their serious burden. Therefore, this meta-analysis study aimed to estimate disrespect and abuse of women during childbirth in East Africa. Methods PubMed, Google Scholar, Scopus, and Science Direct databases were searched. Data were extracted using Microsoft Excel and analyzed using STATA statistical software (v. 14). Publication bias was checked by forest plot, Begg’s rank test, and Egger’s regression test. To look for heterogeneity, I2 was computed, and an overall estimated analysis was carried out. Subgroup analysis was done by study region, sample size, and publication. The pooled odds ratio for associated factors was also computed. Results Out of 654 articles assessed, 18 met the criteria and were included in this study. There were a total of 12,434 study participants. The pooled prevalence of disrespect and abuse of women during childbirth in East Africa was 46.85% (95% CI: 45.26.72–66.98), I2 = 81.9%. It was lower in studies with sample size greater than 5000 (33%). The disrespect and abuse rates between community-based studies (44.96%) and institutional-based studies (47.35%) did not differ significantly, though. Instrumental delivery (AOR = 2.70; 95%CI: 1.79–4.08), presence of complications (AOR = 6.41; 95% CI: 1.36–30.14), receiving care at government hospitals (AOR = 3.66; 95% CI: 1.09–12.23), and poor wealth index (AOR = 2.16; 95% CI: 1.26–3.70) were associated factors. Conclusion In East Africa, disrespect and abuse of women during childbirth was high. Instrumental delivery, presence of complications during childbirth, receiving care at government hospitals and poor wealth index were predictors of maternal disrespect and abuse. Safe delivery practice should be promoted. Training in compassionate and respectful maternity care, particularly in public hospitals, has also been recommended.